Measurements of Natural Radionuclides and 137Cs in Airborne Particulate Samples Collected from Bali and Lombok Islands (Indonesia) - S Syarbaini; W Wahyudi; G. Suhariyono; D. Gunawan; E. Suharguniyawan (PPIKSN-BATAN, 2021)
Bali and Lombok islands are popular resorts and tourist destinations in the world because of their culture and beautiful natural view. The natural and anthropogenic radionuclides content in surface air of Bali and Lombok islands such as 226Ra, 232Th, 40K and 137Cs were measured at 3 monitoring stations in a period from January to December 2016. Aerosol samples were collected using a high volume total suspended particles (TSP) sampler. The activity concentrations of those radionuclides in airborne particulate matter were measured using gamma-ray spectrometry. The results show that the activity concentrations of natural radionuclides 226Ra, 232Th, and 40K ranged from 1.0 to 3.04 µBq/m3, not detected to 1.78 µBq/m3, and 0.03 to 0.49 mBq/m3, respectively. All airborne particulate matter filter samples were found to be lower than the minimum detectable activity for 137Cs, which means that none of 137Cs is originated from atmospheric nuclear weapon test and other sources in surface air of Bali and Lombok islands. Variations of monthly activity concentrations of natural radionuclides were influenced by rainfall during study period. Furthermore, the peak concentrations of radionuclides also occur due to volcanic ash coming from Mount Rinjani eruption.